Inadequacy Revealed and the Transition to Adaptation as Risk Management in New Zealand - Lawrence, Judy; Allan, Sylvia; Clarke, Larissa (Frontiers in Climate, 2021)
Climate change risk is rife with uncertainty. Increased frequency and intensity of flooding and drought and progressive sea-level rise, that compound and cascade and increase risk over time, pose particular difficulties for planning. The risks require institutional and governance frameworks that are tailored to such a dynamic environment. However, most planning frameworks and their practice focus on the societal need for certainty in space and time, to enable investment decisions to be made and activities to be undertaken with some stability. This means risk is framed in a static manner using time-bound planning methods, such as lines on maps and zoning, that lock in people and assets to areas of risk that are exposed to changing risk in time and space. The consequences are being increasingly revealed globally in deltas, inland low-lying areas and at the coast, and will increase unless planning practice becomes more adaptive and anticipates the risks early enough for adjustments to be made. Current decision-making frameworks in New Zealand have been revealed as inadequate for enabling changing and uncertain risks from climate change to be addressed. We discuss how practice under the existing planning framework has exposed people and assets to greater risk, and the challenges in the transition taking place in New Zealand toward an anticipatory adaptive approach. We chart the course of this transition and suggest how current law and practice can support and embed an adaptive direction within the institutional reforms underway for more effective climate risk management.